Comparative Analysis of Revenue Generation and Management of Hotels in Different Locations in Ilorin, Nigeria - Modupe Falabi; Afolabi F.I (CV. Literasi Indonesia, 2021)
Hoteliers clearly believe that location is important for a hotel, and have market research evidence to support this. However, almost nothing has been done to enable this issue to be incorporated into revenue generation. There is a gap in the literature relating to analysis from a location-side approach for increase revenue. This study therefore is untaken to compare revenue generation of hotels with different locations in Ilorin, Nigeria. Two research instruments were used in the study. The first research indictment is the use of a Geographical Positioning System (GPS) while the second is the use of questionnaire. The results of the hypotheses tested shows that there is a significant difference in revenue generated by hotels located in City Centre, sub-urban and highways in Ilorin, significant difference between level of patronage by hotels located in city Centre, sub-urban and highways in Ilorin ; no significant difference in pricing among hotels located in city Centre, sub-urban and highways in Ilorin; significant difference between pricing of services and revenue generated by hotels located in city Centre, sub-urban and highways in Ilorin. The study concludes that revenue will increase if proper management of hotels is being ensured regardless of the hotel locations.